Socio Demographic Factors and Work Performance of Forest Workers in Cajuput Leaf Harvesting at RPH Nglipar, KPH Yogyakarta - Ratih Madya Septiana; Nunuk Supriyatno; Slamet Riyanto (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2020)
Cajuput leaf harvesting is a technical forest activity of non-timber forest products. The productivity of cajuput leaf harvesting is strongly influenced by aspects of human resource capacity and biophysical aspects. This study aims to identify the socio-demographic conditions of forest workers in cajuput leaves harvesting and to analyze the standards performance of harvesting in FMU Yogyakarta. A survey of 100 samples of workers were used to determine socio-demographic characteristics, while in-depth observations were made on 3 workers with different characteristics to determine work performance. The socio-demographic conditions of workers in the cajuput leaf harvesting are seen from eight characteristics, namely age, gender, education, number of dependents, livelihoods, and land ownership. Workers have an average age of 58 years old and are male. The level of education possessed by workers is dominated by graduating from elementary school (SD) by 64 %. The average number of dependents per worker household is 4 people, with the main livelihood being farmers. The average land ownership of workers in cajuput leaf harvesting is 0.17 ha. The work performance of harvesting for normal people in the FMU Yogyakarta is 72.23 kg / hour.